Light-induced non-Arrhenian conductivity of the single crystal methylammonium lead bromide perovskites. (February 2020) - Pospisil, Jan; Zmeskal, Oldrich; Krajcovic, Jozef; Weiter, Martin; Kovalenko, Alexander
Abstract: In the present communication, the conductivity of the single crystal methylammonium lead bromide as a function of temperature is studied. As a result, the activation energies for the dark/light conditions were determined. Interestingly, when the light illumination is applied, depending of the applied bias voltage, the complex conductivity response on the temperature changes was observed. Depending on the electrical field applied, the material follows two behaviors: first is typical of semiconductors and the second one and non-Arrhenian behavior, which is distinctive for metals. This is, for the best of our knowledge, the first observation of this unique property of single crystal methylammonium lead bromide perovskite. Highlights: Light-induced complex conductivity in single-crystal lead halide perovskites was observed. Conductivity dependence on temperature shows semiconductor behavior in the dark. In the light, at bias voltages (~1 V) the overall tendency of the conductivity behavior was preserved. When illumination and high bias voltage were applied the light-generated species behave as free charge carriers. At moderate voltage values (~2 V), both types of conductivities were observed.